Choosing the proper spatial and temporal resolution for water management: Don’t forget the ‘Invisible’ factors - Vosti, S.A.; Torres, M. (2006)
In the search for the proper spatial and temporal resolution at which to manage natural resources, we are generally guided by the flows and stocks of water that we can ‘see’ – rainfall, flowing water, reservoirs, dams, etc. We use what we observe to identify the socially optimal flows/stocks of water, and then suggest the public policy action required to achieve these results. However, there are also some ‘invisible’ factors that need to be included in policy discussions related to water management; one important invisible factor is groundwater (the focus of this brief). The bad news is that groundwater is ‘invisible,’ hence stocks and flows of it are more difficult to measure. The good news is that we are discovering ways to more cheaply measure groundwater stocks/flows and to predict the spatial and temporal effects of groundwater extraction. The SFRB research team has developed a demonstration model capable of examining these effects, and what follows is derived from simulation experiments using that model in the Buriti Vermelho sub-catchment area located near Brasilia. The Buriti Vermelho Sub-Catchment Area The Buriti Vermelho (BV) sub-catchment area is a small watershed comprised of several types and spatial extents of farming activities. Figure 1 depicts the BV site; the precise boundaries of the sub-catchment area are given by the thin black line. Water emerges from about the south-central part of the site, just outside the green patch of cerrado típico (savanna forest) and flows from south to north. Blue circles identify the location and size of capital-intensive centerpivot irrigation schemes, while yellow rectangles identify small farms. Large patches of rainfed agriculture remain in the